(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the benefits created for women in the higher education system, as well as their content and practical significance. It also highlights the role of these benefits in expanding women’s access to education, increasing their social activity, and ensuring gender equality. The article examines measures aimed at supporting women within the framework of state policy and their results.